Infantile obesity: anthropometric and biochemical characteristics - Pajuelo, Jaime (2003)
Objetive: To determine both anthropometric and biochemical characteristics and relationship in children with exogenous obesity. Material and methods: Fifty 6 to 18 year-old children and adolescents (25 male and 25 female) with body mass index (BMI) over 95 percentile according to Must et al classification were studied. Studies included triceps and subscapular skinfolds, waist circumference, serum total cholesterol (TC) and triglycerides (TG). Dyslipidemia was determined with TC 200 mg/dL and 100 mg/dL in children less than 10 year-old and TG 130 mg/dL for persons above 10 years of age. Children were divided in two groups according to 50 p values for BMI, TS and WC. Average and standard deviation were determined in each group, as well as Pearson correlation for both anthropometric and biochemical indicators. Results: A total of 32,6% and 55,6% of obese children and adolescents presented hypercholesterolemia and hypertriglyceridemia, respectively; 26,1% had mixed dyslipidemia. Statistic significant difference (p< 0.05) was found for anthropometric indicators, as opposed to biochemical indicators. Conclusions: Hypertriglyceridemia was the main problem in obese child. Obesity and dislipidemias could be independent risk factors and not necessarily consequence of the other.